(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Biometric payment systems represent a transformative leap in digital finance, offering secure and convenient transactions. In the dynamic Indian market, understanding user experience and trust is pivotal to drive biometric payment adoption. Objectives: This research aims to explore the interplay between user experience and trust in biometric payments in India, identifying factors that shape adoption patterns and providing insights for businesses and policymakers. Key Findings: Participants reported high usability, convenience, satisfaction, and trust in biometric payments. Transaction speed emerged as an area for potential improvement. Correlations revealed positive relationships between user experience variables and trust factors. Qualitative insights underscored the importance of perceived security measures and transparent data handling.